Perceived Constraints in Goat Rearing: Insights from the Goat Banking Attempt in Maharashtra - Patil, Amol P; Chander, Mahesh; Singh, Braj Pal; Verma, Med Ram; Kumari, Maina; Johnson, Demian C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A survey was conducted in 2022 to identify the constraints perceived by the beneficiaries of the Goat Bank of Karkheda, with randomly  selected 300 beneficiaries out of 590 beneficiaries in all; from five districts of Maharashtra state under the jurisdiction of the goat bank.  The data were collected by direct and personal interviews using a pre-tested, semi-structured interview schedule. The Garrett ranking  technique was used to determine the most significant factor (constraint) that was perceived to influence the respondents. The study  identified various constraints perceived to be severe by the goat bank beneficiaries, including shrinkage of grazing land (Mean Score i.e.,  MS 60.70), distant location of veterinary hospital (MS 65.57), poor financial resources (MS 55.40), delayed puberty in goats (MS 61.81),  lesser remunerative prices offered by middlemen (MS 67.13), poor knowledge on scientific goat production (MS 64.44), and mortality in  goats (MS 56.58); under the respective categories of constraints viz. constraints regarding socio-economic status, health management,  feeding management, breeding management, marketing management, care and management, and the general constraints.
Keywords: Garrett ranking; Goat Bank; Mean Score; Perceived constraints